Numerical simulation of particles concentration in wind tunnel model - Tarchid Youcef; Cheriki Idris; HADJ AISSA aissa (Université Amar Thelidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Génie Mécanique, 2022)
Abstract: Aeolian sand transport is defined as the transport of sand particles by wind in various ways, mainly depending on the wind speed and the size and concentration of sand particles. This work aims to numerically simulate this natural phenomenon, specifically the effect of wind speed and the concentration of sand particles inside the wind tunnel. This study was carried out inside wind tunnel 3D model and Stationary using the "COMSOL Multiphysics" program that uses the Euler Euler turbulent flow model, which in turn depends on the turbulent (k-ε) model to solve this type of numerical simulation. One of the most important results of this study is the relationship between wind speed and sand particles concentration in the transport of aeolian sand.
OPTION: ENERGETIC